2017
DOI: 10.1111/ocr.12205
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reliability of landmark‐based, surface‐based and voxel‐based 3D cone‐beam computed tomography superimposition methods

Abstract: Surface-based and voxel-based superimposition methods using the anterior cranial base as a reference structure were accurate and reliable in detecting changes in landmark positions when superimposing. Landmark-based superimposition method was reliable but less accurate than the other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 23 publications
(90 reference statements)
4
70
0
Order By: Relevance
“…(Figure ). Using this technique, Dolphin 3D software combines the voxels in the defined area and automatically superimposed both images . The teeth in the postoperative CBCT were replaced by digital dental models obtained before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…(Figure ). Using this technique, Dolphin 3D software combines the voxels in the defined area and automatically superimposed both images . The teeth in the postoperative CBCT were replaced by digital dental models obtained before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Selecting the particular landmarks to use is one of the most important tasks in the design of morphometric research projects and case studies. Even though landmark‐free approaches to shape analysis are gaining ground (Koehl and Hass, ; Bulut et al, ; Ghoneima et al, ), and even though non‐shape features such as volume and surface area remain relevant (Sholts et al, ; Shearer et al, ; Petaros et al, ), we believe that landmark‐based shape analysis will continue to be a very important research method. One clear advantage of landmarks, compared to landmark‐free approaches, is that it is relatively easy to establish anatomical equivalence or correspondence.…”
Section: Discussionmentioning
confidence: 99%
“…A good superimposition method should be able to register precisely and aid understanding of the changes as a result of growth and/or treatment relative to the structure of reference. According to previous studies, landmark superimposition (Figure ) is similar to 2D cephalometric but more complex, since identifying the landmarks in 3D images can be challenging . Surface ‐based superimposition (Figure ) uses only the “surface” of the 3D structure and requires high‐quality surface for an accurate superimposition .…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing the three methods suggested that landmark superimposition is the least reliable. Surface registration and voxel‐based registration were validated, being the voxel‐based registration associated with less variability . It was also suggested that initial approximation of the images is an important step to reduce registration time of the programme and improve the precision of the superimposition …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation